Impact of Stigma and Community Behavior on Covid-19 Survivors: Literature Review - Ratih Suryandari (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
Coronavirus disease or Covid-19 is a viral infection that was first discovered in Wuhan City, China at the end of 2019. The rapid spread of the disease, the absence of a cure, accompanied by a flood of information through social media, not all of which can be trusted have caused a stigma for people related to Covid-19. The study aims to determine the impact of stigma and community behavior on Covid-19 survivors. The research method uses a literature review, searching for data sourced from PubMed, Google Scholar, Proquest, and Ebsco from March-May 2021. Data analysis was carried out descriptively. The results show that there is an increasing number of reports of public stigmatization of survivors from various environments such as family and work. Stigma arises in social behavior such as ostracizing survivors, refusing and ostracizing people who move from one area to another, ostracizing medical personnel who work in hospitals, refusing corpses because they are considered to have a virus that can be transmitted. Based on these observations, the authors conclude that the freedom of the media in presenting news to give different opinions to everyone, the lack of health educators, the number of hoax news that spread, and the different policies of the central and regional governments that make it difficult to control disease and have an impact on Covid-19 survivors in Indonesia. . rejected the corpse because it was considered that there was still a virus that could be transmitted. Based on these observations, the authors conclude that the freedom of the media in presenting news to give different opinions to everyone, the lack of health educators, the number of hoax news that spread, and the different policies of the central and regional governments that make it difficult to control disease and have an impact on Covid-19 survivors in Indonesia. . rejected the corpse because it was considered that there was still a virus that could be transmitted. Based on these observations, the authors conclude that the freedom of the media in presenting news to give different opinions to everyone, the lack of health educators, the number of hoax news that spread, and the different policies of the central and regional governments that make it difficult to control disease and have an impact on Covid-19 survivors in Indonesia.